Complete genome sequence of Denitrovibrio acetiphilus type strain (N2460T). Issue 3 (May 2010) - Kiss, Hajnalka; Lang, Elke; Lapidus, Alla; Copeland, Alex; Nolan, Matt; Glavina Del Rio, Tijana; Chen, Feng; Lucas, Susan; Tice, Hope; Cheng, Jan-Fang; Han, Cliff; Goodwin, Lynne; et al.
Abstract Denitrovibrio acetiphilus Myhr and Torsvik 2000 is the type species of the genusDenitrovibrio in the bacterial familyDeferribacteraceae . It is of phylogenetic interest because there are only six genera described in the familyDeferribacteraceae .D. acetiphilus was isolated as a representative of a population reducing nitrate to ammonia in a laboratory column simulating the conditions in off-shore oil recovery fields. When nitrate was added to this column undesirable hydrogen sulfide production was stopped because the sulfate reducing populations were superseded by these nitrate reducing bacteria. Here we describe the features of this marine, mesophilic, obligately anaerobic organism respiring by nitrate reduction, together with the complete genome sequence, and annotation. This is the second complete genome sequence of the orderDeferribacterales and the classDeferribacteres, which is the sole class in the phylumDeferribacteres . The 3, 222, 077 bp genome with its 3, 034 protein-coding and 51 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.